The reality behind the pharmaceutical industry, postmodernity with no mercy - Allan Rodríguez Artavia (Universidad de Costa Rica, 2014)
The following article analyzes the current need in the light of the principles of the (post) modernity about the pharmaceutical industry. For its formulation, we conducted a literature review in the databases of the Virtual Health Library (BIREME), and the Scientific Electronic Library Online (SciELO), where after applying predetermined inclusion criteria, it was possible to obtain a total of 23 items that served as the analysis base. Between the main results obtained in thirteen of the documents analyzed it criticizing the marketing process that has set as standard to follow in pharmaceutical production. In seven of the articles it is argued that by in pharmacological industry, there is limited access to medicines in countries or regions with less purchasing power, as there is reluctance to fund research related to diseases that are not profitable. It conclude that given currently own processes of neoliberal policies and capitalism that surround pharmaceutical production, lost focus on the health of the community, transforming such right in a process of marketing and commercialism.